2014
DOI: 10.5058/stresskagakukenkyu.29.84
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors associated with chronic distress in mothers of young children 2 years after the Fukushima nuclear accident

Abstract: The 2011 earthquake and tsunami in Japan caused a meltdown at Fukushima nuclear power plant. This paper examines the association between demographics or exposure to potentially upsetting events following Fukushima disaster and psychological and physical well-being of mothers with young children 2 years after the Fukushima nuclear accident. The sample consisted of mothers with preschool children still inhabiting in low level radiation contamination area, 30~90 km distant from the plant. In addition to exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…55 Rates of positively screened individuals fluctuated to a more considerable degree in studies using convenience samples. The rates tended to be higher in vulnerable populations, such as evacuees living in temporary housing, 24 mothers of young children, 84 nurses, 57 caregivers, 19 and NPP workers. 75 Only one study reported no significant difference in PTSS between the study and the control groups among the medical school volunteers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…55 Rates of positively screened individuals fluctuated to a more considerable degree in studies using convenience samples. The rates tended to be higher in vulnerable populations, such as evacuees living in temporary housing, 24 mothers of young children, 84 nurses, 57 caregivers, 19 and NPP workers. 75 Only one study reported no significant difference in PTSS between the study and the control groups among the medical school volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…About two-thirds of the examined papers (n = 51; 64.6%) were written in English whereas 28 (35.4%) were written in Japanese. 15,18,25,26,29,35,[47][48][49][50]51,54,56,62,63,[66][67][68]70,72,77,81,84,86,88,91,92 Most studies (57; 75.0%) had a single-wave, cross-sectional design. A small portion of the studies had multiple waves of cross-sectional design (n = 15; 19.0%) 15,20,23,27,28,34,35,52,55,[58][59][60][61]87,88 ; among them, three studies (3.8%) conducted a trajectory analysis.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation